Febuxostat‐Induced Agranulocytosis: An Illustrative Case Report and Comprehensive Literature Review - Liu, Qiuping; Zhong, Bing (Clinical case reports, 2025)
ABSTRACT Neutropenia induced by febuxostat is uncommon, with limited literature available to assess its frequency. This rare complication carries a serious risk to life. It is essential for healthcare providers to stay alert and informed about this potential adverse reaction.